2009
DOI: 10.1007/s10509-009-0227-z
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for asteroseismology

Abstract: The observational basis for asteroseismology is being dramatically strengthened, through more than two years of data from the CoRoT satellite, the flood of data coming from the Kepler mission and, in the slightly longer term, from dedicated ground-based facilities. Our ability to utilize these data depends on further development of techniques for basic data analysis, as well as on an improved understanding of the relation between the observed frequencies and the underlying properties of the stars. Also, stella… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 96 publications
(90 reference statements)
5
46
0
Order By: Relevance
“…As seen, only a few stars, including the Sun, actually adhere to the expectation from the asymptotic relation. This was similarly found by Christensen-Dalsgaard & Houdek (2010) 7 for α Cen A (Bedding et al 2004), while α Cen B (Kjeldsen et al 2005) was found to fulfill the asymptotic relation. As explained by Christensen-Dalsgaard & Houdek (2010) this reflects a rapid variation of the sound speed in the core of α Cen A from its more evolved state due to its higher mass compared to the B component.…”
Section: Average Seismic Parameterssupporting
confidence: 72%
See 1 more Smart Citation
“…As seen, only a few stars, including the Sun, actually adhere to the expectation from the asymptotic relation. This was similarly found by Christensen-Dalsgaard & Houdek (2010) 7 for α Cen A (Bedding et al 2004), while α Cen B (Kjeldsen et al 2005) was found to fulfill the asymptotic relation. As explained by Christensen-Dalsgaard & Houdek (2010) this reflects a rapid variation of the sound speed in the core of α Cen A from its more evolved state due to its higher mass compared to the B component.…”
Section: Average Seismic Parameterssupporting
confidence: 72%
“…This was similarly found by Christensen-Dalsgaard & Houdek (2010) 7 for α Cen A (Bedding et al 2004), while α Cen B (Kjeldsen et al 2005) was found to fulfill the asymptotic relation. As explained by Christensen-Dalsgaard & Houdek (2010) this reflects a rapid variation of the sound speed in the core of α Cen A from its more evolved state due to its higher mass compared to the B component. Similarly, Verma et al (2014) found an increasing departure from the asymptotic description of the oscillation frequencies while fitting the signatures of the acoustic glitches.…”
Section: Average Seismic Parameterssupporting
confidence: 72%
“…In this respect, asteroseismology is thought to be the most powerful tool for studying the inner properties of stars through the observation of stellar oscillations (e.g. Aerts et al 2008;Christensen-Dalsgaard & Houdek 2010, and references therein).…”
Section: Effects Of Mixing In Semiconvective Layersmentioning
confidence: 99%
“…[26] determined the profile of opacity enhancements that would make a solar model with AGSS09 abundances have the same structure as Model S by [27]. This standard solar model was evolved with the classic GN93 abundances (dashed, black curve in Fig.…”
Section: Opacity Solutions To the Solar Abundance Problemmentioning
confidence: 99%